2013
DOI: 10.1002/chem.201300078
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive and Selective Fluorescent Probe for Cysteine Based on a New Response‐Assisted Electrostatic Attraction Strategy: The Role of Spatial Charge Configuration

Abstract: A new strategy for fast fluorescent detection of cysteine (Cys), based on a response-assisted electrostatic attraction, is demonstrated. By utilizing this strategy, we designed and synthesized three fluorescent probes for the specific detection of Cys under actual physiological conditions. The probe m-CP, a coumarin fluorophore conjugated with a substituted methyl pyridinium group through an unsaturated ketone unit, showed highly selective and sensitive detection for cysteine (Cys) over homocysteine (Hcy) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…The isomers of 58, 58 0 were synthesized for evaluating the spatial influence of electrostatic interactions. 94 Cys adducts of 58 0 underwent rapid cyclization to a non-fluorescent thiazepine derivative, presumably due to the destabilization of the zwitterionic form. The results indicated that the proper spatial electrostatic interaction played a significant role in the selectivity and kinetics during the sensing process.…”
Section: Aromatic Substitution-rearrangement Reactionmentioning
confidence: 99%
“…The isomers of 58, 58 0 were synthesized for evaluating the spatial influence of electrostatic interactions. 94 Cys adducts of 58 0 underwent rapid cyclization to a non-fluorescent thiazepine derivative, presumably due to the destabilization of the zwitterionic form. The results indicated that the proper spatial electrostatic interaction played a significant role in the selectivity and kinetics during the sensing process.…”
Section: Aromatic Substitution-rearrangement Reactionmentioning
confidence: 99%
“…The majority of studies that sought to detect Hcy and Cys have failed in distinguishing these molecules because of their similar spatial arrangement and chemical reactivity . Recently, several studies detected Cys by using chemodosimetric probes through Michael‐type reaction . In contrast to Cys, a few methods enabled the selective discrimination of Hcy.…”
Section: Methodsmentioning
confidence: 99%
“…As a well-known thiol-containing amino acid in this family, Cys serves as the building block in protein synthesis, detoxification, and metabolism in live organisms Chen et al, 2013;Chen et al 2013;Li et al, 2009;Das et al, 2012). Alterations in the level of cellular Cys has been implicated with neurotoxicity, and the deficiency of Cys may lead to many syndromes, such as a hematopoiesis decrease, slow growth, hair depigmentation, leucocyte loss, psoriasis and so on (Shiu et al, 2011;Yin et al, 2013;Shao et al, 2011;Zhou et al, 2013;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%